PENGARUH PERMEN KARET XYLITOL SETELAH TERAPI SCALING DAN ROOT PLANING TERHADAP SPESIES MIKROBIOTA ORAL DALAM SALIVA ANAK STUNTING - Ernesto, Gian; Ilmiawati, Cimi; Desmawati, Desmawati; Juwita, Dinda Ratna; Effendi, Muhammad Dzaky Sayyid; Wirza, Thifla Rafifa; Bobby, Bobby; Abdani, Fathan Alif (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: Stunting is a condition caused by chronic malnutrition, which affects physical, cognitive, and oral health in children, including gingivitis. Reduced salivary flow in stunted children disrupts oral hygiene and increases the risk of oral infections due to oral microbiota dysbiosis. Aim: This study aimed to evaluate the effect of xylitol chewing gum as an adjunct to Scaling and Root Planing (SRP) therapy in improving oral health and microbiota in stunted children. Methods: Eighteen stunted children aged 6-12 years with gingivitis were randomly assigned to two groups: the SRP group (n=9) and the SRP + xylitol chewing gum group (n=9). SRP was performed to reduce gingival inflammation, and xylitol chewing gum was administered for 14 days following SRP. Clinical parameters were assessed using the Gingival Index (GI) and the Oral Hygiene Index-Simplified (OHI-S). Saliva samples were collected before and after treatment for microbiota profiling using 16S rRNA metagenomic sequencing. Results: In the control group (SRP), the average GI score significantly decreased (p=0.00), but the reduction in OHI-S scores did not show a statistically significant difference (p=0.06). In the SRP + xylitol group, there was a significant reduction in both GI (p=0.00) and OHI-S scores (p=0.00). Microbiota analysis showed an increase in beneficial bacteria and a reduction in pathogenic species, particularly in the SRP + xylitol group. Conclusion: SRP is effective in reducing gingival inflammation in stunted children, and the addition of xylitol chewing gum further improves oral health by enhancing salivary flow and modulating the oral microbiota. This combined therapy may offer a promising strategy for improving oral health in children with stunting